Hypernatremia in Newborn Due to Uncontrolled Maternal Diabetes Insipidus - Kyungmi Lee; Eun Sun Kim; Kee Hyun Cho (Korean Society of Neonatology, 2021)
Neonatal hypernatremia often occurs in poorly breastfeeding infants, and rehydration without complications is the primary treatment. However, the etiologies and management for neonates who present with hypernatremia immediately after birth are not well reported. In this case report, we describe a neonate with hypernatremia and hyperosmolality, born to a mother with oligohydramnios of unknown etiology. Meticulous fluid therapies considering the time to physiologic diuresis were successfully performed, and the underlying cause was determined to be an uncontrolled maternal central diabetes insipidus.